2011
DOI: 10.5607/en.2011.20.2.85
|View full text |Cite
|
Sign up to set email alerts
|

Microarray Screening for Genes Involved in Oligodendrocyte Differentiation in the Zebrafish CNS

Abstract: Within the vertebrate nervous system, myelination is required for the normal function of neurons by facilitating the rapid conduction of action potentials along axons. Oligodendrocytes are glial cells which myelinate axons in the central nervous system. Disruption of myelination and remyelination failure can cause human diseases such as multiple sclerosis. Despite the importance of myelination, the molecular basis of oligodendrocyte differentiation and myelination are still poorly understood. To understand the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Of note, one of the altered genes derived from microarray data analysis and verified by qRT-PCR and IHC was Dlg1 (Fig. 9B) (Chung, 2011). Previous studies reported that physical interaction between scaffolding protein DLG1 (Discs large homolog 1, also termed synapse-associated protein 97, SAP97) and APC is required for polarization of the microtubule cytoskeleton in astrocytes (Etienne-Manneville et al, 2005; Nathke, 2006).…”
Section: Resultsmentioning
confidence: 97%
“…Of note, one of the altered genes derived from microarray data analysis and verified by qRT-PCR and IHC was Dlg1 (Fig. 9B) (Chung, 2011). Previous studies reported that physical interaction between scaffolding protein DLG1 (Discs large homolog 1, also termed synapse-associated protein 97, SAP97) and APC is required for polarization of the microtubule cytoskeleton in astrocytes (Etienne-Manneville et al, 2005; Nathke, 2006).…”
Section: Resultsmentioning
confidence: 97%
“…Although Sox10 is a robust marker for many neural crest lineages, Sox10-driven lines also label some other non-neural crest-derived cell populations at later time points. For example, multiple studies have used Sox10:eGFP and Sox10:mRFP to mark oligodendrocytes (Chung, Kim, Kim, Bae, & Park, 2011;Kucenas, Snell, & Appel, 2008) and otic epithelial cells (Carney et al, 2006;Kwak et al, 2013). To determine if Sox10:zFucci is also expressed in these cell types, we crossed the Sox10:zFucci line with either the Sox10:mRFP or Sox10:eGFP line.…”
Section: Resultsmentioning
confidence: 99%
“…Several groups have also taken a microarray approach to discover novel genes in oligodendrocyte development (Chung et al, ; Takada and Appel, ). One microarray screen (Takada and Appel, ) looked at transcripts from cells purified by fluorescent activated cell (FAC) sorting from tg( olig2 :EGFP) zebrafish.…”
Section: Zebrafish As a Model For Studying Myelinationmentioning
confidence: 99%